2016
DOI: 10.1515/cipms-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Status of rats myocardium under subchronic mercury exposure and its pharmacological correction

Abstract: The article is devoted to the characteristics of the myocardium restructuring under the influence of 0.01 LD50 mercury (II) chloride, in rats, under subchronic exposure, and the correction of the detected changes. In the work, the structural and metabolic reorganization of myocardium was studied by way of general histological, histochemical and electron microscopic techniques. Herein, administration of Unithiolum reduces the severity of reactions to toxic effects of mercury salts: decreases the intensity of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Heavy metals may be found in soil, water, air, and are used in everyday life (Tsuzuki, Sugiyama, & Haramaki, ; Sokurenko & Chaikovskii, ; Van Sprang, et al, ; Sokurenko & Chaikovskii, ; Sokurenko, Savchyna, Litus, Kaminsky & Chaikovsky, ). Once in the body, they excessivly accumulate in the tissues causing the whole range of symptoms of poisoning (such as abdominal discomfort, vomiting, weight loss, heart and kidney failure, alimentary syndrome, neuromuscular syndrome (more often seen in adults), cerebral syndrome, lead encephalopathy, neurological defects, psychopathological disorders (Kamynsky, Primachenko, Sokurenko, and Chaikovsky, ; Rostislav, Liudmyla, and Yuri, ; Doudi & Setorki, ) at the same time making the liver, which is one of the main organs of detoxification, suffer (Hadrup & Lam, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals may be found in soil, water, air, and are used in everyday life (Tsuzuki, Sugiyama, & Haramaki, ; Sokurenko & Chaikovskii, ; Van Sprang, et al, ; Sokurenko & Chaikovskii, ; Sokurenko, Savchyna, Litus, Kaminsky & Chaikovsky, ). Once in the body, they excessivly accumulate in the tissues causing the whole range of symptoms of poisoning (such as abdominal discomfort, vomiting, weight loss, heart and kidney failure, alimentary syndrome, neuromuscular syndrome (more often seen in adults), cerebral syndrome, lead encephalopathy, neurological defects, psychopathological disorders (Kamynsky, Primachenko, Sokurenko, and Chaikovsky, ; Rostislav, Liudmyla, and Yuri, ; Doudi & Setorki, ) at the same time making the liver, which is one of the main organs of detoxification, suffer (Hadrup & Lam, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the neuroprotective effect of Thiotriazoline, Mildronate and Magnesium B6 in mercury toxication was found [21,22]; it was shown that under subchronic mercury exposure and combined pharmacological protection with Unithiol and Quercitin, myocardial structures restored due to the positive effect on the hemomicrocirculatory bed [10].…”
Section: Introductionmentioning
confidence: 99%